VizieR Online Data Catalog: SMC RR Lyrae Fourier decomposition (Kapakos+, 2012) - Kapakos, E.; Hatzidimitriou, D. (VizieR Online Data Catalog, 2013)
The present study is based on observations obtained with the 1.3m Warsaw telescope at the Las Campanas Observatory, Chile, during phase III of the OGLE project, between 2001 and 2009 (Soszynski et al., 2010, cat. J/AcA/60/165) (3 data files).
Keywords: Magellanic Clouds; Magnitudes; Stars: variable